Construction of Smart City Development Index in Indonesia - Nabil Miftah Irfandha (Proceedings of The International Conference on Data Science and Official Statistics, 2021)
Development in urban areas requires city management to solve problems that occur because of high population growth. The complexity of the issues in urban areas varies widely, including a decrease in the quality of public services, reduced availability of residential land, congestion on the highway, excessive energy consumption, waste accumulation, increased crime rates, and other social problems. City assessment tools can be used as support for decision-making in urban development as they provide assessment methodologies for cities to show progress towards defined targets. In the 21st century, there has been a shift from sustainability assessment to developing smart cities. The construction of the Smart City Development Index (SCDI) is considered capable of providing a basis for formulating effective and efficient solutions in reducing existing city problems. The purpose of this study is to find out the general description and get the factors that form SCDI; get the results of SCDI measurements; examine the uncertainty analysis and sensitivity analysis of SCDI, and see the relationship between SCDI and HDI (Human Development Index). Based on the results of factor analysis, there are six factors formed where the highest SCDI with a population of fewer than 200,000 people in Madiun City (East Java Province), the highest SCDI with a population between 200,000 to 1,000,000 people in Yogyakarta City (DI Yogyakarta Province) and the highest SCDI with a total population of over than 1,000,000 people in Tangerang City (Banten Province). The results of uncertainty analysis and sensitivity analysis show that the formed SCDI is robust and reliable. In general, SCDI has a positive relationship to Human Development Index (HDI). The construction of this index aims to facilitate local and central governments in reviewing policies regarding the distribution of funds so that the smart city's development is by existing conditions.